Study of Literature on Business Ethics for Entrepreneurs - Manullang, Elisa Betty; Simarmata, Primus Paroloan (Universitas Negeri Medan, 2023)
Bank Indonesia as the monetary authority is responsible for the smooth running of the payment system. In general, the payment system in Indonesia is divided into two, namely the cash payment system and the non-cash payment system. In the cash payment system, the tools used are in the form of currency or commonly called banknotes and coins as a means of payment. Then in the non-cash payment system, the tools used are Card-Based Payment Instruments, bilyet giro, checks, debit notes, and the latest instruments, namely electronic money. The range of cashless payment systems is divided into two types of transactions, namely transactions with large transaction values (wholesale) and retail transactions. While the number of entrepreneurs in Indonesia is still recorded at 0.43% of the total productive age population, this figure is very far behind neighboring countries, such as Singapore where the number of entrepreneurs has reached 7%, Malaysia 5%, and Thailand 3%. Meanwhile, according to the chairman of KPPU said that in 2017 the number of entrepreneurs in Indonesia ranged from 1.6% - 1.8% of the total population in Indonesia. This number is still very far from the standards of developed countries with a minimum number of entrepreneurs of 2% of the total productive age, to overcome this the government seeks to create 20,000 new entrepreneurs and the development of 1,200 Small and medium industry centers or can be called SMIs. In this article, we provide an idea from Bank Indonesia for business ethics for entrepreneurs. The method used in this article is to study the literature and review some of the references obtained. So it is hoped that this idea will have a good impact on readers and provide changes for Indonesian entrepreneurs in the future.